Simulation of reactor transients in vver-1000 for pretraining of operating personnel - M. A. Volman (Известия высших учебных заведений: Проблемы энергетики)
The pretraining system for NPP operating personnel in WWER-1000 is proposed. The basis of this system is computer simulation of reactor transients. The software packages and procedural guides for mathematical simulation of nuclear reactor kinetics are developed. The results of numerical experiments for the mode of fast deep primary circuit shut-down cooling are described. The simulation procedures on an analytical simulator of power unit for different technological modes are developed. The guidelines and operation manuals are adopted for this purpose. The simulation of protection and blocking is described in more detail.